Gas chromatographic determination of water and ethanol in silage by internal standard method - Huida, Lea (Agricultural and Food Science, 1982)
Water and ethanol contents of different silages were determined by solvent extraction gas chromatography. Methanol was used as internal standard. The gas chromatograph was equipped with thermal conductivity and hydrogen flame ionization detectors. Glass columns, length 1.5m, i.d. 2 mm, were packed with Chromosorb 101, 80/100 mesh size. Water and ethanol extractions of 10 silages and gas chromatographic runs of the extracts could be carried out daily. The methods are suitable for routine laboratory analysis and use of the internal standard allows the gas chromatographic runs to be performed faster and more accurately. The precisions of water and ethanol determinations were satisfactory, the mean relative standard deviation percents of 12 replicate analyses being respectively 0.22 and 2.55. Water content of silages was also determined by conventional forced-air oven drying at 105°C. When ethanol content of the silage was above 5 percent, there was a tendency for water contents obtained by the oven drying method to be over 5 percentage units greater than those obtained by solvent extraction gas chromatography. When the ethanol content was below 0.5 percent, high acetic acid and lactic acid contents with low pH resulted the same tendency, the difference between the methods varring from 0.5 to 2.2 percentage units.